Expanding the forms of visual representation. The First International Festival of Architectural Films at the 8th UIA Congress, Paris 1965 - González Cubero, Josefina (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2025)
Researching on cinema as a means of creation, diffusion, and propaganda of the image of architecture, as well as the construction of our collective imaginaries and the symbolic appropriation of spaces, is also to work in favor of architecture. Therefore, to approach the relationship between architecture and cinema in international meetings of architects, where ideas were exchanged while architectural cinema was exhibited and awarded, is the general objective of this work in order to recover the knowledge of what existed and has disappeared from memory. The specific objective is to focus it on the event that consecrated the official union between both technical arts: the First International Festival of Architectural Films at the 8th Congress of the International Union of Architects (Union Internationale des Architectes, UIA), held in Paris in 1965. The text responds to a historiographic approach that investigates an archeology of documentary cinema linked to architecture and is a pioneer in identifying and inventorying the qualified filmography as an audiovisual framework in which the professional meetings took place, as well as their influence among the Spanish architects who attended. Recovering this heritage of the re-presentation and re-production of architecture is crucial for the training of students, which in recent times has been inexorably linked to these audiovisual media of communication and dissemination of information.